Cutaneous Sarcoidosis – Diagnostic Challenges - Florica SANDRU; Mihai Cristian DUMITRASCU; Adelina POPA; Daniel-Vasile BALABAN; Razvan-Cosmin PETCA; Raluca Gabriela MIULESCU (Modern Medicine)
Sarcoidosis is a multisystemic granulomatous disease, with unknown etiology, characterized histopathologically by the development in the affected organs of some „empty” (non-caseous) granulomas. Cutaneous lesions can sometimes be the first localization of the disease. We present the case of a patient with known sarcoidosis and autoimmune thyroiditis, who developed a rash spread on the trunk and limbs, for which she was treated with dermatocorticoids and antihistamines, but without significant improvement. A skin biopsy was performed with histopathological examination, which revealed: at the dermal level, lympho-histiocytic infiltrates with nodular distribution, forming several granulomas, without areas of necrosis of caseification, including frequent cells with epithelioid appearance, suggestive for the diagnosis of cutaneous sarcoidosis. The patient underwent systemic cortisone therapy and hydroxychloroquine, with favorable outcome. The challenge of diagnosing this pathology is to differentiate it from a number of conditions, including: ring granuloma, cutaneous Crohn’s disease, lipoid necrosis, lupus vulgaris. To establish the diagnosis of certainty, it is necessary to correlate the clinical data with the result of the histopathological examination.